CLOZE TECHNIQUE AND READING PROFICIENCY: CAUSAL COMPARATIVE ANALYSIS TO ELEVENTH GRADERS - Mega Sanja Imelda; Ary Setya Budhi Ningrum; Sri Wahyuni (Widya Mandala Surabaya Catholic University, 2022)
The reading proficiency of Indonesian students is still relatively low, especially the reading performance in English as a foreign language. Thus, it needs several explorations on the technique suitable for students with diversities of reading competence. This study describes the effect of implementing the cloze procedure on teaching reading proficiency. The research method employed the design of quantitative causal-comparative. The population is the students of the second grade of senior high school with the samples involving two classes. To collect the data, the pre-test and post-test were applied to the classes. The result of the test was analyzed by using ANCOVA. The result shows that the sig. is higher than 0.05 (0.92 > 0.05). It reveals that the cloze procedure is not significantly effective in teaching reading particularly on hortatory exposition. However, the result shows that both the students who get the cloze technique and those who do not get that procedure, perform an enhancement on their post-test despite the insignificant difference.